The Influence of Social Support and Ability Perception on Coping Strategies for Competitive Stress in Soccer Players: The Mediating Role of Cognitive Assessment - Dai, Zhao; Liu, Qiang; Ma, Wenhui; Yang, Chengwei (Frontiers in Psychology, 2021)
Objective: To explore the effect of social support and ability perception on stress coping strategies for competitive stress, and to reveal the mediating effects of primary and secondary evaluation, so as to further improve the theoretical model of stress coping in soccer players. Methods: Athletes from 22 teams in the Chengdu Middle School Campus Football League were taken as survey samples, and surveys were conducted on their stress experience, social support, ability perception, cognitive assessment, and coping strategies for competition stress. SPSS 21.0 and AMOS 21.0 statistical analysis software were used in this data analysis and process, description statistics, correlation analysis, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to process the obtained data. Results: 1) Positive primary assessment acted as a full mediator in the relationship between social support and secondary assessments, and negative primary assessment acted as a partial mediator in the relationship between competence perception and secondary assessments; 2) Secondary assessment played a partial mediating role between positive primary assessment positive and positive coping strategies, and a full mediating role between negative primary assessment and positive coping strategies; 3) Secondary assessments played the mediator neither between social support and a coping strategy for stress nor competence perception and a coping strategy for stress 4) Positive primary assessment, positive negative assessment, and secondary assessment all had significant positive benefits for positive coping. Still, the impact of positive primary assessment on positive coping was significantly better than negative primary assessment and secondary assessment. Conclusion: The coping strategy for the competitive stress model proposed by this study has a very good fit for the causal model. It can be used to explain the observed data from soccer players in middle schools. The primary and secondary assessments play different roles in the model. The combination of problem focuses and emotional focus on the positive stress coping strategy is suitable in the field of competitive sports. Still, the relevant research results need to be further explored and verified in the future.